Sistemas agrícolas e adubação na biomassa e óleo essencial de lavanda (Lavandula dentata L.) - Silva, Sérgio Macedo (2015)
Lavender is grown commercially for the production of essential oil to obtain various products of perfumery and aromatherapy. In the case of aromatic species, the presence of oxygenated monoterpenes can ensure medicinal properties and therapeutic effects of essential oils. On the other hand, the content and the chemical composition of essential oil depends on different factors such as climate, geographical origin, harvest and mineral nutrition, which can significantly affect the quality and quantity of production. The objective of this study was to investigate the influence of organic and organicmineral fertilizers associated with the protected cultivation to production and essential oil of lavender (Lavandula dentata L.). Two experiments were conducted in the years 2012 and 2013 in the environmental conditions of Uberlândia, MG. The experimental design was a randomized complete block design in a split plot with five replications, testing both systems (field and greenhouse) and two types of fertilizers (mineral and organic). The second experiment was also in a complete randomized block design, with four replications. The treatments consisted of different doses of a NPK (10-10-10) organic- mineral fertilizer with 8% of organic carbon from the recommendation of 500 kg ha-1, 100% (T1), 80% (T2) 60% (T3), 40% (T4) and 20% (T5), beyond the recommended mineral fertilization of 500 kg ha-1 formulated in NPK (10-10-10) (T6). Three harvest of flowers and one of leaves were performed. The first experiment, the greenhouse showed higher biomass of flowers and leaves of lavender in relation to the field, but in terms of fertilization there was no statistical difference between the fertilizers. The plants grown in the greenhouse showed higher oil yield. The second experiment, biomass productivity (flowers and leaves) of L. dentata in greenhouse was higher than in the field during the rainy season. In the field and in the greenhouse, the amount of productivities of successive crops can result in more than 6 t ha-1 and 8 t ha-1 biomass, respectively. Dose of 60% of the organic-mineral provides good essential oil revenues and lavender biomass productivity. As for the essential oil, were found more than 20 substances in the essential oil of L. dentata in both experiments, and the major compounds were cineole, camphor and fenchone. In the first experiment, mineral or organic fertilization did not influence the production of the major constituents of lavender. In the second experiment, the chemical composition of lavender was affected by environmental conditions and season of harvest.